Determining Strategies on Playing Badminton using the Knuth-Morris-Pratt Algorithm - Lala Septem Riza; Muhammad Irfan Firmansyah; Herbert Siregar; Dian Budiana; Alejandro Rosales-Pérez (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Mastery techniques in badminton game are a main ability that must be possessed by players. One part of these techniques is the strategy in proper shuttlecock placement, so that the opposing player is difficult to restore it. Therefore, this study aims to build a computational model and its implementation that are able to provide predictions/recommendations for trainers and players on determining strategies of shuttlecock’s placements and strokes. The proposed model takes into account historical game patterns that have been done by world class athletes. Then, string matching using the Knuth-Morris-Pratt algorithm and a clustering method are utilized to provide solutions to be some strategies on shooting the shuttlecock. The model is then implemented in the R programming language. Several experiments, involving 20 series of world matches collected as historical data, have been conducted to validate the system. From the results obtained, it can be concluded that the system can be used as an alternative tool for players and coaches to determine the strategy in the placement and strokes of shuttlecock on badminton game.